Respuesta :

Answer:

Step-by-step explanation:

1. (x - 3)(x + 7) = 0

  By zero product property,

  (x - 3) = 0 ⇒ x = 3

  (x + 7) = 0 ⇒ x = -7

2. (2x + 6)(x - 7) = 0

   2(x + 3)(x - 7) = 0

   By zero product property,

   (x + 3) = 0 ⇒ x = -3

   (x - 7) = 0 ⇒ x = 7

3). (4x - 2)(x + 4) = 0

   2(2x - 1)(x + 4) = 0

   (2x - 1) = 0 ⇒ x = [tex]\frac{1}{2}[/tex]

   (x + 4) = 0 ⇒ x = -4

4. (5x - 1)(3x + 9) = 0

   3(5x - 1)(x + 3) = 0

   By zero product property,

   (5x - 1) = 0 ⇒ x = [tex]\frac{1}{5}[/tex]

   (x + 3) = 0 ⇒ x = -3

5. (x - 8)(x + 2) = 0

   By zero product property,

   (x - 8) = 0 ⇒ x = 8

   (x + 2) = 0 ⇒ x = -2